The Effect of Reggio Emilia Approach on Children's Creativity from the Islamic Psychology Review - Madyawati, Lilis; Maemonah, Maemonah (Jurnal Tarbiyatuna, 2021)
The development of self-creativity in children needs to be performed because they possess the interests and talents that are expected to be honed or developed. Therefore, this study aims to test the effect of the Reggio Emilia approach on children's creativity from the Islamic Psychology review. A total of 36 students aged 5-6 years were selected as participants using purposive sampling. Data were collected using the pre-experiment with One Group Pretest-Posttest Design. The result showed that children's creativity increased through aptitude and non-aptitude. This study indicates that 22 and 14 students had Islamic verbal creativity in the average and above-average category respectively. Therefore, the Reggio Emilia approach positively affects children's creativity.